EVALUASI PERLAKUAN AKUNTANSI ASET TETAP MENURUT PSAK NO. 16 (REVISI 2014) DI RUMAH SAKIT PALANG BIRU KUTOARJO - , (Politeknik Sawunggalih Aji, 2022)
Palang Biru Kutarjo Hospital is one of the agencies that provide health services to the community. To make this happen, hospitals need a variety of medical equipment to support the operational activities of hospitals. Good asset management is needed so that the equipment that has been owned can be maintained and can be used optimally, not quickly damaged until the specified life span. Asset management as in PSAK 16 (revised 2014), namely recognition, measurement, depreciation, termination and release as well as presentation and disclosure of fixed assets in financial statements, has been applied in the asset management policy of the Hospital. So that this can be done properly and properly, discipline and evaluation need to be done. The purpose of this study is to find out whether the treatment of fixed assets in the hospital is appropriate or there are still deviations. If deviations are found, improvements are recommended. Based on the results of observations made on the data obtained can be concluded as follows : The accounting treatment for recognition, measurement, depreciation, method of write-off and disposal as well as disclosure and reporting of fixed assets at the Palang Biru Kutoarjo Hospital of23 item evaluated 65% is in accordance with the provisions of PSAK 16 (2014 revision), and 35% are not in accordance with PSAK 16 (2014 revision) Keywords: Treatment of Accounting, Fixed Assets, Hospitals